An advanced electrical heating technique for double-sided Y(Gd)BCO coated conductor: gaining high engineering current density based on MOCVD. (12th November 2021) - Yang, Fan; Zhao, Ruipeng; Tao, Bowan; Chen, Xi; Huang, Tao; Fei, Xi; Chen, Tingyu; Xia, Tao; Chang, Yongtao
Abstract: An advanced electrical heating technique was proposed and adopted for the reel-to-reel deposition of double-sided Gd x Y1− x Ba2 Cu3 O7− δ (Y(Gd)BCO) films on the surface of LaMnO3 /epitaxial-MgO/IBAD-MgO/Y2 O3 /Al2 O3 /Hastelloy tapes based on the metal organic chemical vapor deposition process. In this technique, heating current is introduced into alloy tape to produce heat through the electric brushes. The use of thin Hastelloy tapes is an effective method to obtain a high engineering current density. However, the reduction of the substrate thickness will directly attenuate its mechanical strength, which will lead to the deformation of tapes at high temperature based on original electric heating device. More seriously, the electrical contact between the alloy substrate and the brush will deteriorate, which could cause ignition and ablation at the edge of the tapes. Therefore, in order to improve mechanical and electrical stability, we redesigned a novel electrical heating device to deposit Y(Gd)BCO films. Furthermore, through adopting the multiple-deposition process based on the new electrical heating device, the J e of Y(Gd)BCO film can reach 900 A mm −2 (at self-field, 77 K), which has been significantly improved compared with the J e before optimization.